Effect of Freshwater Soaking Durations on Salt Reduction and Nutrient Composition of Turbinaria murayana Seaweed for Poultry Feed - Reski, Sepri; Rusli, Ridho Kurniawan; Mahata, Maria Endo; Rizal, Yose (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This study aims to reduce the salt content in Turbinaria murayana seaweed before its incorporation into poultry feed by soaking it in fresh water at a 1:50 w/v ratio. The experimental design follows a completely randomized design with five treatments and four replications. The treatments involved soaking durations of 1, 2, 3, 4, and 5 days in freshwater. Data were analyzed using Analysis of Variance (ANOVA), and treatment differences were assessed using Duncan's Multiple Range Test. The results indicated that different soaking durations in freshwater effectively reduced the salt content and increased the dry matter and organic matter percentages of Turbinaria murayana seaweed. A soaking duration of 2 days is particularly effective, resulting in a salt content of 0.61%, a salt reduction percentage of 95.79%, a moisture content of 12.86%, a dry matter content of 87.14%, and an organic matter content of 71.13%.